The Level of Public Awareness in Paying Zakat to The National Zakat Amil Agency in North Toraja District - Farhan, Ilham; Agussalim, Agussalim; Nuringsih, Nuringsih; Trimulato, Trimulato (Nuban Jagadhita Centre, 2024)
Purpose: This article aims to determine the level of public awareness of paying zakat in Baznas. Methodology: The type of research used is quantitative research. The data collection techniques used are observation, questionnaire, and documentation. The data analysis techniques used are descriptive statistical analysis and multiple linear regression test analysis. Findings: The result of the research obtained is that there is a strong relationship between the level of public awareness and zakat payment in North Toraja Regency. This significant correlation indicates that the higher the public awareness, the greater their contribution to paying zakat through BAZNAS. Further analysis shows that the level of public awareness plays an important role in explaining the proportion of zakat payment, although other factors beyond awareness also affect the final result that are not examined in this study.